Diagnosis of a single gallbladder with double cystic ducts and dominant accessory duct draining into the right hepatic duct: a case report - Cheng-Hsien Wu (SAGE Publishing, 2021)
Biliary anomalies are a high risk for biliary injury during surgery, and although a biliary anomaly is occasionally encountered, variations in cystic ducts are rare. A preoperative diagnosis is highly valuable in facilitating surgical procedures and avoiding surgical complications. Herein, the case of a 67-year-old female patient with acute cholecystitis, in which preoperative fluoroscopic cholangiography clearly demonstrated a single gallbladder with double cystic ducts, is presented. The accessory duct was found to be dominant, draining into the otherwise normal right intrahepatic bile duct, and laparoscopic cholecystectomy was performed smoothly and successfully. Fluoroscopic cholangiography is a powerful tool that may clearly depict the anomaly of a single gallbladder with double cystic ducts. Through appropriate preoperative knowledge and demonstration of this biliary anomaly in the present case, laparoscopic cholecystectomy was safely performed, and the patient was symptom-free at the 3-year follow-up assessment.